PENERAPAN TEORI BELAJAR HUMANISTIK DALAM PEMBELAJARAN - Perni, Ni Nyoman (Institut Hindu Dharma Negeri Denpasar, 2018)
Students are human beings whose human identity as a conscious subject needs to be defended and enforced through educational systems and models that are